Using the IUCN Environmental Impact Classification for Alien Taxa to inform decision‐making - Sabrina Kumschick; Sandro Bertolino; Tim M. Blackburn; Giuseppe Brundu; Katie E. Costello; Maarten de Groot; Thomas Evans; Belinda Gallardo; Piero Genovesi; Tanushri Govender; Jonathan M. Jeschke; Katharina Lapin; et al. (Conservation Biology, 2024)
The Environmental Impact Classification for Alien Taxa (EICAT) is an important tool for biological invasion policy and management and has been adopted as an International Union for Conservation of Nature (IUCN) standard to measure the severity of environmental impacts caused by organisms living outside their native ranges. EICAT has already been incorporated into some national and local decision‐making procedures, making it a particularly relevant resource for addressing the impact of non‐native species. Recently, some of the underlying conceptual principles of EICAT, particularly those related to the use of the precautionary approach, have been challenged. Although still relatively new, guidelines for the application and interpretation of EICAT will be periodically revisited by the IUCN community, based on scientific evidence, to improve the process. Some of the criticisms recently raised are based on subjectively selected assumptions that cannot be generalized and may harm global efforts to manage biological invasions. EICAT adopts a precautionary principle by considering a species’ impact history elsewhere because some taxa have traits that can make them inherently more harmful. Furthermore, non‐native species are often important drivers of biodiversity loss even in the presence of other pressures. Ignoring the precautionary principle when tackling the impacts of non‐native species has led to devastating consequences for human well‐being, biodiversity, and ecosystems, as well as poor management outcomes, and thus to significant economic costs. EICAT is a relevant tool because it supports prioritization and management of non‐native species and meeting and monitoring progress toward the Kunming–Montreal Global Biodiversity Framework (GBF) Target 6.